RELATIONSHIP BETWEEN EDUCATION AND ECONOMIC GROWTH IN INDONESIA, MALAYSIA AND SINGAPORE - Alkeelani A, Alkeelani Abdulsalam; Haryati, Titik (Universitas Negeri Semarang, 2017)
History shows that education was originally held informally in the family and held informal in society. Furthermore, formal education was held also in school. Even as you are understandable, these days the world of education experienced rapid development is outstanding. Relationships Education and Economic Life very closed. In connection with the problems as questionable above, based on data obtained from various sources, Sudarja Adiwikarta (1988) concluded that a link is steady and positive between the degree of education with economic life, in the sense that the higher the degree of education the higher the degree of economic life. Education is an essential ingredient of prosperity is at once obvious and contentious. So in this research will analyze the relationship between education (number of school or facilities and school expenditure) and economic growth (GDP). In this research will focused on high school. The reason to choose education because education reflects the country development index especially also in the economic growth.This research will used quantitative research. Data collection method in this research is documentation. Data collection from 1990-2015 from World Bank for data Indonesia, Malaysia and Singapore. Technique analysis data used is normality test, regression model, and correlation analysis, also descriptive analysis. The decsriptive analysis method is a method that describe mean, minimum value, maximum value, and standard deviation.The result showed that there is relationship between education expenditure and GDP in Indonesia, Malaysia and Singapore, this can be seen from the significant value lower than 0,05 so the hypothesis accepted. Another result showed that there is relationship between number of high school and GDP in Indonesia. This can be seen from the significant value lower than 0,05 so the hypothesis accepted. Suggestion for further research is to add another variables that affecting GDP in Indonesia, Malaysia and Singapore, such as employment rate, inflation rate.